Proceedings of the 2017 International Conference on Manufacturing Engineering and Intelligent Materials (ICMEIM 2017) 2017
DOI: 10.2991/icmeim-17.2017.86
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution and Thermodynamic Analysis of Inclusions in Gear Steel after Magnesium Treatment

Abstract: Abstract.The influence of different magnesium content on the inclusions in steel was studied under the condition of the same molten steel at 1873 K. The results show that, after the magnesium treatment, the tiny MgO•Al 2 O 3 inclusions could become the nucleus of MnS in solidification of liquid steel, which weakens the large number of MnS precipitates in grain boundaries. The change of the oxide core in the composite sulfides with the increase of magnesium content is: Al 2 O 3 →MgO•Al 2 O 3 →MgO•Al 2 O 3 +MgO→… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…It is found that the attraction between MgO and MgO-Al 2 O 3 inclusions is 1/10 of that between Al 2 O 3 particles, which indicates that MgO and MgO-Al 2 O 3 are not easy to aggregate and grow up. Jie Xu et al [7] studied the influence of different magnesium content on inclusions in steel at steelmaking temperature. It is found that magnesium aluminate spinel formed after magnesium modification can be used as the core of manganese sulfide precipitation, which reduces the precipitation of rod-shaped manganese sulfide at grain boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the attraction between MgO and MgO-Al 2 O 3 inclusions is 1/10 of that between Al 2 O 3 particles, which indicates that MgO and MgO-Al 2 O 3 are not easy to aggregate and grow up. Jie Xu et al [7] studied the influence of different magnesium content on inclusions in steel at steelmaking temperature. It is found that magnesium aluminate spinel formed after magnesium modification can be used as the core of manganese sulfide precipitation, which reduces the precipitation of rod-shaped manganese sulfide at grain boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Wang [ 17 ] studied the modification route of rare earth yttrium (Y) on alumina inclusions: Al 2 O 3 → Y 2 S 3 + YAlO 3 + Al 2 O 3 → Y 2 S 3 + YAlO 3 + Y 2 O 2 S + YAlO 3 + Al 2 O 3 → Y 2 S 3 + Y 2 O 2 S. Rare earth La and Ce are lanthanide elements which have research significance for the modification of inclusions. There are many thermodynamic studies on the treatment of Al 2 O 3 inclusions with rare earth in molten steel [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. There are few studies on the addition of rare earth-treated Al 2 O 3 inclusions with high-carbon steel as experimental raw material; reports on the kinetic surface in particular are limited [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth La and Ce are lanthanide elements which have research significance for the modification of inclusions. There are many thermodynamic studies on the treatment of Al 2 O 3 inclusions with rare earth in molten steel [18][19][20][21][22][23][24]. There are few studies on the addition of rare earth-treated Al 2 O 3 inclusions with high-carbon steel as experimental raw material; reports on the kinetic surface in particular are limited [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many studies have been conducted to explore the effects of the inclusions on the machinability of the non-quenched and tempered steel [6][7][8][9][10][11][12][13][14]. Studies have shown that the sulfide in the steel mainly exists in the form of MnS [15], one of most harmful inclusions.…”
Section: Introductionmentioning
confidence: 99%